The gievn equation is: -

P+Q = a (P-Q)

How can get this form: Q = {(a-1) / (a+1)}P from the above equation?

Printable View

- Mar 19th 2011, 12:50 PMarijit2005Need Help. Confusing Equation
The gievn equation is: -

P+Q = a (P-Q)

How can get this form: Q = {(a-1) / (a+1)}P from the above equation? - Mar 19th 2011, 12:54 PMTheChaz
You'll need to get all terms with a "Q" in them on one side.

P + Q = aP - aQ

P + aQ + Q = aP

aQ + Q = aP - P

Factor!

Q(a + 1) = P(a - 1)

Divide by (a + 1)

$\displaystyle Q = P *\frac{a - 1}{a + 1}$